2018
DOI: 10.1016/j.drugalcdep.2018.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol use in pregnant women with substance use disorder

Abstract: This study demonstrates a high prevalence of prenatal alcohol use in early pregnancy in both groups, while patients with SUD/OUD consume more alcohol. These findings underscore the need for targeted screening and intervention for alcohol use in all pregnant women, especially those with SUD/OUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The median number of drinks consumed per individual per week during the periconceptional period (defined as 2 weeks before and 2 weeks after the last menstrual period) was 3.5 drinks in the general obstetrics cohort versus 5.5 drinks in the OUD cohort, a statistically significant difference. 49 Similarly, the median number of binge drinking episodes in early pregnancy (defined as the last menstrual period to pregnancy recognition) was 1 episode in the general obstetrics cohort versus 3 episodes in the OUD cohort, also statistically significant. 49 Given the risks of NAS and FAS, studies such as the one by Bakhireva et al, further underscore the need for screening and intervention for alcohol use during pregnancy, perhaps especially for women with OUD.…”
Section: The Concurrent Use Of Opioids and Alcohol Among Pregnant Womenmentioning
confidence: 84%
See 1 more Smart Citation
“…The median number of drinks consumed per individual per week during the periconceptional period (defined as 2 weeks before and 2 weeks after the last menstrual period) was 3.5 drinks in the general obstetrics cohort versus 5.5 drinks in the OUD cohort, a statistically significant difference. 49 Similarly, the median number of binge drinking episodes in early pregnancy (defined as the last menstrual period to pregnancy recognition) was 1 episode in the general obstetrics cohort versus 3 episodes in the OUD cohort, also statistically significant. 49 Given the risks of NAS and FAS, studies such as the one by Bakhireva et al, further underscore the need for screening and intervention for alcohol use during pregnancy, perhaps especially for women with OUD.…”
Section: The Concurrent Use Of Opioids and Alcohol Among Pregnant Womenmentioning
confidence: 84%
“…49,50 Overall, the lack of research is surprising given that aggregate data from the 2005 to 2014 NSDUH indicate that, among pregnant women who used opioids non-medically, almost half reported alcohol use and nearly one-third binge drinking in the past 30 days. 51 In one of the two studies (mentioned above) that focused on the concurrent use of opioids and alcohol during pregnancy, Bakhireva et al 49 analyzed data from the ENRICH (Ethanol, Neurodevelopment, Infant and Child Health) prospective birth cohort study, which compared the prevalence of selfreported alcohol use among women receiving prenatal care from general obstetrics clinics (n = 365) with women receiving prenatal care from an OUD program (n = 295), and found significant differences in the intensity of alcohol consumption between the two study cohorts. The median number of drinks consumed per individual per week during the periconceptional period (defined as 2 weeks before and 2 weeks after the last menstrual period) was 3.5 drinks in the general obstetrics cohort versus 5.5 drinks in the OUD cohort, a statistically significant difference.…”
Section: The Concurrent Use Of Opioids and Alcohol Among Pregnant Womenmentioning
confidence: 99%
“…As AUDs are associated with neurobiological adaptations that reduce an individual’s cognitive control, clinicians must be non-judgmental, non-directive, and private [ 37 , 38 ]. Empathy and mutual respect are also important as previous research has found a positive association between these factors and recovery from substance abuse among pregnant women [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of biomarkers to detect substance exposure such as hair, urine, blood, and meconium (Bakhireva et al, 2018;Bearer et al, 1999;Gutierrez et al, 2015;Ostrea Jr, Brady, Gause, Raymundo, & Stevens, 1992) has enhanced exposure identification. However, biomarkers which rely on metabolic evidence in body tissue, by their very nature, primarily identify recent use.…”
Section: Considerations For Accurate Measurement Of the Independent Vmentioning
confidence: 99%